Pembelajaran pendidikan jasmani di masa pandemi covid-19: Analisis respon siswa dan guru dalam menggunakan google classroom - Dirmawanysah; Gazali, Novri; Nanda, Fitri Agung (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
During the Covid-19 pandemic, there was a change in the learning system from face-to-face to technology-based learning through online media. This study aims to determine the responsiveness of students and teachers in using Google Classroom media during the Covid-19 pandemic. This is a mixed method research (quantitative and qualitative) using questionnaires and interviews as instruments. The subjects of this study were 89 students and 1 physical education teacher. The data analysis technique used is to calculate the percentage value of the final questionnaire score. Based on the results of the study, it was revealed that the use of Google Classroom media in physical education learning achieved a questionnaire score percentage of 93.69%. Meanwhile, the physical education teacher's response shows that the use of Google classroom in physical education learning during the current Covid-19 pandemic is very helpful in the online learning process and has been implemented properly. Even though the research results revealed a good response in using google classroom, this research has limitations, namely the research subject and only examines the use of one media, namely google classroom so that the research reach is limited. The results obtained are expected to be able to make a reference for further research, especially in the use of learning media during the Covid-19 pandemic in physical education learning so that learning outcomes are maximized.